Alveococcus multilocularis in the Arctic fox (Alopex lagopus) in the Arctic zone of Yakutia - L. M. Kokolova; L. Yu. Gavrileva; I. M. Okhlopkov (Российский паразитологический журнал, 2023)
The purpose of the research is to study of infection of white foxes (Alopex lagopus) with alveococcosis in the Arctic zone of Yakutia and to perform molecular genetic study of Alveococcus multilocularis.Materials and methods. To determine the Alveococcus infection in the Arctic fox in the Arctic zone of Yakutia, 19 specimens were studied in 2018, 27 specimens in 2019, 51 specimens in 2020 and 119 specimens in 2021 by complete and partial dissections of the gastrointestinal tract, other organs and tissues. The species identification of detected helminths was performed using the Identification Guide of Helminths in Carnivorous Mammals in the USSR (D. P. Kozlov, 1977). The collected helminths were fixed in 70% alcohol. Nineteen samples were studied by polymerase chain reaction (PCR) to determine A. multilocularis isolates.Results and discussion. In the Russian Federation, A. multilocularis is widespread in Yakutia, Chukotka, Magadan Region, Krasnoyarsk, Altai, and Khabarovsk Territories, and other regions. In the Arctic zone, Arctic foxes are 100% infected with A. multilocularis. The parasite circulates among wild animals, mainly polar foxes and Arctic lemmings (Dicrostonyx torquatus Pallas, 1778). Agricultural and wild ungulates become infected by ingesting parasite eggs, and dogs become infected by eating organs and tissues affected by multilocular alveococcosis. There is a risk of transmission of A. multilocularis to humans. A person becomes infected in processing the skins of arctic foxes obtained in hunting, and through contact with infected domestic carnivores. An increase in white fox populations and in their infection rate including A. multilocularis was found in the tundra zone. In the Arctic zone of Yakutia, A. multilocularis form that was close to the North American N1 strain was found.